Sports service quality for event venues: evidence from Malaysia. Issue 2 (6th May 2014) - Ho Voon, Boo; Lee, Nagarajah; Murray, Duncan
Abstract : Purpose: – The purpose of this paper is to empirically test the proposed measure of sports service quality (SSQ) and examine the relationships between emotional experience (EE) and user satisfaction (US) for sports competitions/training venues (i.e. for the sport of badminton). Design/methodology/approach: – Focus group discussions and related literature review were used to generate items for the SSQ. Structured questionnaires captured the perceptions of 240 users of sports venues in Malaysia. The relationships between SSQ, EE and US were assessed via structural equation modelling (SEM). Findings: – Results show that the SSQ has five dimensions (peripheral, reliability, responsiveness, core and value). Core, peripheral and value have positive effects on users' EE whereas peripheral, reliability, responsiveness and core have positive effects on US. The SEM analysis suggests that EE mediates the relationship between SSQ and US. Research limitations/implications: – The SSQ scale is developed using data from the badminton sport industry and is yet to be validated in other types of sports venues. In addition, measures of customer loyalty also need to be considered. Practical implications: – Findings suggest that provision of quality service directly influences satisfaction with sports venues and enhances the EE of customers. Sports venue managers should monitor the service management, particularly in terms of the physical environment and personnel. Originality/value: – This paper proposes a specific measure of service quality tailored for use in sports venues. It also provides further support for the mediating role EE plays in the service quality-satisfaction relationship.